Transcriptional activation of BolBCAT4 genes enhanced aliphatic glucosinolate accumulation in cabbage - Yan, Chengtai; Zhang, Jiahao; Yang, Wenjing; Liu, Yao; Bai, Xue; Zeng, Qi; Liu, Xifan; Ren, Yanjing; Shao, Dengkui; Li, Baohua (Frontiers in Plant Science, 2025)
Aliphatic glucosinolates are a large group of plant-specialized metabolites in Brassica vegetables, and some of their degradation products are key nutrients with significant beneficial effects on human health. Increasing the nutritional quality is one of the central research questions and breeding goals for Brassica vegetables. Major progress has been made in understanding transcriptional regulation of aliphatic glucosinolates biosynthesis in the model plant, while little is known about it in Brassica vegetables. In this study, we used cabbage to study the transcriptional regulation of BolBCAT4 genes, the first set of biosynthetic genes in methionine-derived aliphatic glucosinolate metabolism, and identified and functionally validated four upstream positive regulators of BolBCAT4 genes, BolMYB3R, BolbHLH153, BolMED4 and BolERF74, with consistent phenotypic effects of inducing short-chain aliphatic glucosinolates, including glucoraphanin. Our work confirmed the biological functions of BolBCAT4 genes, identified dozens of candidate upstream regulators, and provided valuable regulatory mechanisms and breeding targets for enhancing the nutritional quality of cabbage.